2016
DOI: 10.3390/ijerph13050493
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Parent’s Perception on Air Quality—From the Individual to the Community Level

Abstract: The perception of air quality significantly affects the acceptance of the public of the government’s environmental policies. The aim of this research is to explore the relationship between the perception of the air quality of parents and scientific monitoring data and to analyze the factors that affect parents’ perceptions. Scientific data of air quality were obtained from Wuhan’s environmental condition reports. One thousand parents were investigated for their knowledge and perception of air quality. Scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…The first reason is relevant to the degree of perception and concern about air pollution in different tourist groups. The previous studies have confirmed that people's opinions about the severity of air pollution largely depend on their sociodemographic status, including education, knowledge, income, and so on [59,60]. For instance, tourists with higher income levels are typically more sensitive to air pollution than those with low income [39].…”
Section: Discussionmentioning
confidence: 80%
“…The first reason is relevant to the degree of perception and concern about air pollution in different tourist groups. The previous studies have confirmed that people's opinions about the severity of air pollution largely depend on their sociodemographic status, including education, knowledge, income, and so on [59,60]. For instance, tourists with higher income levels are typically more sensitive to air pollution than those with low income [39].…”
Section: Discussionmentioning
confidence: 80%
“…However, local government reports show that an increase of privately owned motor vehicles is the largest contributor of current air pollution in Wuhan [27].…”
Section: Discussionmentioning
confidence: 99%
“…China (Ban et al, 2017;Fan et al, 2017;Guo et al, 2016;Huang et al, 2017;Liao et al, 2015;Qian et al, 2016) active travel for low income school children aged 9-10 years and they analysed the potential of such schemes for future trails which can be adopted and implemented by schools. This study identified that the mode of transport of school children in Great Britain is largely dependent on cars for even short distances, for instance, 19% of very short distance (~1.6 km) trips to schools and short distance trips (ranging from 1.6 to 3.2 km) to primary schools are done by cars.…”
Section: Community Empowermentmentioning
confidence: 99%